LAW ENFORCEMENT AGAINST FOREIGN FISHERMEN PERPETRATORS OF ILLEGAL FISHING CRIMES IN INDONESIA - Ardiyansah; Tofik Yanuar Chandra; Mohamad Ismed (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
This study aims to analyze the legal provisions regarding the criminal act of illegal fishing in Indonesian laws and regulations and to analyze law enforcement against foreign fishermen who are perpetrators of illegal fishing in Indonesian marine areas. This research is a normative legal research by using the Statute Approach, Conceptual Approach, Comparative Approach and Case Approach. The data analysis method is done by descriptive analytical, which is to describe the results of research with data as complete and detailed as possible in handling illegal fishing crimes in Indonesian marine areas. The results of this study indicate that the legal provisions regarding the criminal act of illegal fishing in Indonesian laws and regulations are regulated in Law Number 45 of 2009 Amendment to Law Number 31 of 2004 concerning Fisheries, where if a suspect foreign citizen (WNA) is arrested, but the state of Indonesia does not yet have an agreement with the country from which the foreigner is from.